Considering the Action of Degrading Water Quality on the Electrochemical Response of Sulphide Minerals - Ndamase, Nolihle (Department of Chemical Engineering, 2022)
Mining operations in arid regions are compelled to reduce their consumption of fresh water. Closed water circuits are an attractive solution and, in addition to reducing freshwater consumption, they have the added benefit of reducing reagent consumption as well as the environmental impact of mining operations by eliminating effluent discharge. Water is used as a liquid medium as well as a means of transportation during mining operations. Flotation, in particular, is a water intensive process where water makes up about 80- 85% of the pulp phase. Process water contains organic and inorganic species which accumulate as they are recycled. To avoid the treatment costs of removing these contaminants, many mining operations allow the quality of their water to degrade over time. When this water is introduced into flotation circuits the pulp chemistry is altered. Ionic species that accumulate in recycled process water have been shown by previous studies to be especially deleterious to flotation performance. Such ions include Ca2+, Cu2+, Mg2+, Pb2+, SO4 2- and S2O3 2- , to name a few. One of the effected flotation sub-processes is collector adsorption which is responsible for inducing hydrophobicity on valuable mineral surfaces. Accumulating ionic species have been shown to hinder collector adsorption which reduces the recovery of valuable minerals to the concentrate. Consequently, degrading water quality threatens the economic viability of mining operations that make use of closed water circuits. Xanthates are the most widely used collectors to treat base metal sulphide minerals. Most sulphide minerals are semi-conductors and xanthate adsorption onto their surfaces takes place via electrochemical reactions. Numerous studies have investigated the effect of degrading water quality on xanthate adsorption however there is very limited understanding as to how this takes place from an electrochemical perspective. This study therefore aims to investigate how the presence of accumulating ionic species at varying concentrations affects the electrochemical adsorption of sodium ethyl xanthate onto chalcopyrite and galena. Synthetic plant water (SPW) was used to mimic the composition of recycled process water. The synthetic plant water used in this study comprised of single salt solutions to isolate the effects of the ionic species of interest which were Cl- , Mg2+, SO4 2- and S2O3 2- . The salts used were NaCl, MgCl2, MgSO4, Na2SO4 and Na2S2O3. The ionic strengths were varied between 0.0242 M, 0.0727 M, 0.1212 M and 0.2426 M which correspond to 1, 3, 5 and 10SPW, respectively. Measuring the mineral rest potentials is an electrochemistry technique that was used to monitor how changing water quality affected xanthate-mineral interactions. Microflotation measurements were conducted to observe how changing water quality affected mineral floatability. Zeta potential measurements were used to determine the mineral surface charge and assess which of the ions of interest were active on the mineral surfaces. This study also aimed to investigate if electrochemistry techniques such as rest potential measurements can be used to predict flotation performance with changing water quality. Microflotation measurements revealed that degrading water quality only had an impact on the initial flotation kinetics of chalcopyrite and galena with both minerals achieving final recoveries greater than 90% regardless of changing water quality. The only exception was galena in the presence of the S2O3 2- ion where final recoveries were no greater than 35%. The S2O3 2- ion was found to be the most deleterious ionic species on both chalcopyrite and galena floatability, more especially on the latter. This was attributed to the formation of xanthyl and metal thiosulphate species which passivate the mineral surfaces, hindering collector adsorption. The formation of xanthyl thiosulphate species also reduces the amount of xanthate available for inducing hydrophobicity. It was hypothesized that increasing the ionic strength of the synthetic plant water would result in a greater hindrance of collector adsorption due to the competition between ionic species and xanthate for adsorption onto the mineral surface. This was partially true as the initial chalcopyrite recoveries in the presence of the S2O3 2- ion decreased with increasing ionic strength. Additionally, the highest initial galena recoveries in NaCl, MgCl2 and Na2S2O3 were achieved at 1SPW indicating that, even though the correlation was not linear, the initial galena recoveries in these salts decreased with increasing ionic strength. Contrastingly, the highest initial chalcopyrite recoveries in NaCl, MgCl2 and Na2SO4 were achieved at 10SPW indicating that increasing the ionic strength resulted in higher recoveries. This improvement in initial recovery with increasing ionic strength was attributed to the compression of the electrical double layer which causes the mineral-water and air-water interfaces to destabilize thus reducing bubble-particle attachment time. Rest potential measurements revealed that dixanthogen and lead xanthate were likely the dominant surface reaction species formed on chalcopyrite and galena during collector adsorption, respectively. The only exceptions were chalcopyrite in the presence of Cl- at 5SPW and S2O3 2- above 1SPW where the species that was favoured to form in these conditions was cuprous xanthate. Rest potential measurements also revealed that the presence of the S2O3 2- ion hindered xanthate-mineral interactions to a greater extent than any other ion of interest. It was hypothesized that rest potential measurements can be used as a quick and easy technique to assess the effect of changing water quality on the flotation performance of sulphide minerals. This is due to the ability of rest potential measurements to indicate the extent of xanthate-mineral interactions. Unfortunately, rest potential measurements failed to consistently predict flotation performance with changing water quality. They did however successfully predict the depressant effect of the S2O3 2- ion on the floatability of both minerals, especially that of galena. Zeta potential measurements indicated that all the ions of interest were active on the mineral surfaces. This confirmed the assertations made in previous studies that these ionic species are surface-active counter-ions that hinder collector adsorption and therefore mineral floatability due to mineral surface passivation. For example, the surface activity of the divalent cation Mg2+ had a stronger effect on mineral floatability than the monovalent Cl- anion. This was proposed to be due to the formation of the insoluble metal hydroxide Mg(OH)2 which rendered the mineral surfaces hydrophilic resulting in lower recoveries.